Giant Pediatric Supratentorial Tumor: Clinical Feature and Surgical Strategy - Zhang, Zhong-Ding; Fang, Huang-Yi; Pang, Chen; Yang, Yue; Li, Shi-Ze; Zhou, Ling-Li; Bai, Guang-Hui; Sheng, Han-Song (Frontiers in Pediatrics, 2022)
Purpose: To analyze the clinical character of giant pediatric supratentorial tumor (GPST) and explore prognostic factors. Materials and methods: We analyzed the clinical data of 35 cases of GPST from single center between January 2015 and December 2020. The tumor volume was measured by 3D slicer software based on preoperative magnetic resonance imaging (MRI). Glasgow Outcome Scale (GOS) was used to evaluate the short-term prognosis. Result: The tumor volume varied from 27.3 ml to 632.8 ml (mean volume 129.8 ml/ median volume 82.8 ml). Postoperative histopathological types include ependymoma, pilocytic astrocytoma, choroid plexus papilloma (CPP), craniopharyngioma, primitive neuroectoderm tumor (PNET), choroid plexus carcinoma (CPC), immature teratoma, atypical teratoid rhabdoid tumor (AT/RT), anaplastic astrocytoma and gangliocytoma. Tumors in children younger than three years and tumors located at the hemispheres appeared to be larger than their respective counterparts, though no statistical significance was found. A patient with giant immature teratoma died during the operation because of excessive bleeding. Postoperative complications include CSF subgaleal collection/effusion, infection, neurological deficits and seizures. The mean GOS score of GPST patients in 6 months is 3.43±1.12, and 83% of patients (29/35) showed improvement. Favorable GPST characteristics to indicated better GOS included small tumor (≤100ml) (P=0.029), low-grade (WHO I-II) (P=0.001), and gross total resection (GTR) (P=0.015). WHO grade was highly correlated with GOS score (correlation coefficient =-0.625, P<0.001). GTR and tumor volume were also correlated (correlation coefficient =-0.428, P=0.010). Conclusion: The prognosis of GPST is highly correlated with the histopathological type. Smaller tumors are more likely to achieve GTR and might lead to higher GOS score. Early diagnosis and GTR of the tumor are important for GPST management.